2019
DOI: 10.14744/tjtes.2019.46595
|View full text |Cite
|
Sign up to set email alerts
|

Atypical femoral fractures related to bisphosphonate use: a comprehensive review of 19 patients

Abstract: BACKGROUND: Atypical femur fracture is a rare complication of bisphosphonate treatment, which is widely used for the prevention of osteoporotic fractures. This study aims to report clinical and radiological features and outcomes of surgically treated atypical femur fractures related to bisphosphonates. METHODS: We retrospectively reviewed patients with the diagnosis of atypical femur fracture who were under bisphosphonate treatment and who were surgically treated in our clinic between January 2009 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…1 ). Among 29 studies, 11 cohort articles included both sites of AFF (subtrochanteric and midshaft), 7 13 16 17 18 19 20 21 22 23 24) 9 cohort studies reported outcomes after surgery of subtrochanteric AFFs, 6 9 10 11 14 25 26 27 28) and 9 single cohort studies reported midshaft AFF. 8 12 15 29 30 31 32 33) The overall incidence of nonunion was 10.3% (77 / 742) in total, 17.5% (52 / 297) in the subtrochanteric AFFs group, and 5.6% (25 / 445) in the midshaft AFFs group ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). Among 29 studies, 11 cohort articles included both sites of AFF (subtrochanteric and midshaft), 7 13 16 17 18 19 20 21 22 23 24) 9 cohort studies reported outcomes after surgery of subtrochanteric AFFs, 6 9 10 11 14 25 26 27 28) and 9 single cohort studies reported midshaft AFF. 8 12 15 29 30 31 32 33) The overall incidence of nonunion was 10.3% (77 / 742) in total, 17.5% (52 / 297) in the subtrochanteric AFFs group, and 5.6% (25 / 445) in the midshaft AFFs group ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although bisphosphonates are known to have a relation to AFF, this may suggest that other factors play a greater role in the healing process of these fractures such as malreduction, which may decrease the contact area between the main fragments. 7 14 19) However, cessation of bisphosphonate after surgery of AFF should be recommended according to the guidelines of American Society for Bone and Mineral Research. 40) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPs inhibit bone resorption and formation. Recently, many cases of AFF caused by the application of low energy have been reported [1][2][3]. Severely suppressed bone turnover (SSBT) is also reported as one of the main causes of AFF [1,4,5].…”
Section: Introductionmentioning
confidence: 99%